Community college faculty engagement in the scholarship of teaching and learning. Issue 195 (31st August 2021) - Harrington, Christine; Lyken‐Segosebe, Dawn; Braxton, John M.; Nespoli, Lawrence A.
Abstract: This study evaluated the connection between community college faculty engagement in the scholarship of teaching and learning (SoTL) and student success by investigating the frequency of individual community college faculty members engagement in activities that comprise the SoTL categories of classroom research and pedagogical content knowledge.